Reverse the Lens, Set Focus on the Followers: A Theoretical Framework of Resource Dependence, Upward Influence, and Leadership - Tripathi, Neha (Frontiers in Psychology, 2021)
Leadership theories predominantly focus on top-down managerial influence on the employees. Recent theoretical developments however accentuate call for scholarly attention on holistic models comprising both leadership and followership. In the present paper, drawing on resource dependence theory, the author develops a theoretical framework of upward influence and leadership construction. The author proposes a novel outlook illuminating upward influence in hierarchical relationships whereby employees, as the hosts of tacit resources, inculcate interdependent relationship with the manager. Considering dependence of the employee and the manager on each other for tangible and intangible resources, relationships, (a) power imbalance and (b) joint or embedded dependence, emerge. The author further explains leadership construction in power imbalance and embedded relationships and elaborates on organizational and team structural boundary conditions. By revitalizing upward influence, the proposed theoretical framework offers new insights to leadership and followership literatures with a potential to change the conversation from a foundational thesis assuming managerial capacity to lead and bestow resources to the subordinates to a two-way resource dependence perspective, scarcely considered in the contemporary management research.